2011
DOI: 10.1007/s00894-011-1202-5
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of ONIOM method for the study of NH3 dissociation at open ends of BNNTs

Abstract: The reliability of ONIOM approach have been examined in calculations of adsorption energies, transition structures, change of HOMO-LUMO energy gaps and equilibrium geometries of the interaction between NH(3) and N-enriched (A) or B-enriched (B) open ended boron nitride nanotubes. To these ends, four models of the A or B, with different inner and outer layers have been studied. In addition, various low-levels including, AM1, PM3, MNDO and UFF have been examined, applying B3LYP/6-31 G* in all high-levels. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…A negative or positive value of E dis is referred to as an exothermic or endothermic process. The B3LYP/6-31G* is the commonly used level of theory in investigations of nanotube systems [23][24][25][26][27][28]. However, we improved it by adding the polarization pfunction to basis sets of hydrogen atoms (the second star) to get a high-quality description of H 2 dissociation process.…”
Section: Computational Detailsmentioning
confidence: 98%
“…A negative or positive value of E dis is referred to as an exothermic or endothermic process. The B3LYP/6-31G* is the commonly used level of theory in investigations of nanotube systems [23][24][25][26][27][28]. However, we improved it by adding the polarization pfunction to basis sets of hydrogen atoms (the second star) to get a high-quality description of H 2 dissociation process.…”
Section: Computational Detailsmentioning
confidence: 98%
“…In previous studies, widely in chemical processes the various nanostructures because of their sensitivity and activity have been used and results have been shown that functionalization of na-nostructure can improvement the capability of nanostructures to detect toxic gases. [13][14][15][16][17] In previous papers the adsorption of various gases such as SO 2 , H 2 S, CO 2 and CO on surfaces of nanostructures have been investigated. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Zaboli and et al 35 the adsorptions of the H 2 S, H 2 Se and SO 2 molecules on the surface of fullerene by the density functional theory investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to C-NCS, there are other nanocone sheets which are found experimentally such as carbon germanium nanocone sheets (CGe-NCS). [11][12][13][14][15][16][17][18][19] In the current study, the interactions of C 2 Cl 2 gas with C-NCS and CGe-NCS with disclination angles of 240° exploring its potential application as C 2 Cl 2 gas sensor will be theoretically investigated. The N functionalization of nanostructures is very important and it can effectively change the electronic structures of nanostructures.…”
Section: Introductionmentioning
confidence: 99%